Numerical simulation of fluid mud layer under current and waves in estuaries and coastal areas - Chung, Dang Huu (Vietnam Journal of Mechanics, 1998)
The formation and development of fluid mud layer under the both factors of current and wave that often happens in estuaries and coastal areas are studied in detail through numerical simulation on the basis of the 2D shallow water equations for tidal flow, the advection-diffusion equation for cohesive sediment transport and the equations for fluid mud transport. At the same time the model for wave propagation is also included. Numerical solution of a special case for a part of the Severn estuary is obtained using the finite difference method as an illustration of the applicability of the model in practice.